The phenomenon of the Holocaust as an inspiration for writers – based on the novel by Roma Ligocka’s Dziewczynka w czerwonym płaszczyku - Krzesłowska, Nadia (Inspiration, 2019)
The article deals with the issue of inspiration through the work of culture. It tells the fate of a Jewish woman, Roma Ligocka, who – after seeing Spielberg’s film Schindler’s List, devoted to the drama of World War II – was inspired by a film image to write a book about her own extremely traumatic war experiences, which she experienced as a child. These events have left its mark throughout her adult life. The novel proves that Nazi crimes have left a mark on the psyche of many lives.